CASE STUDY OF THE LOCAL WISDOM OF THE BADUY TRIBE IN PRESERVING THE RIVER - Wahid Dzulhaji; Nur Fadhilah Awaliyah; Muhammad Faisal Fahrudin Firdaus; Eneng Liah Khoiriyah (Hikamatzu | Journal of Multidisciplinary, 2025)
The natural philosophy of the Baduy people is very strong. The Baduy people strongly maintain balance and harmony with nature. As a result, they strongly defend the teachings about protecting and preserving nature. That is what makes the Baduy people coexist with nature in harmony. In addition, the Baduy people do not exploit natural resources; Instead, they use what is available with preservation. The Baduy people have the belief that nature is one of the almighty trusts that must be maintained and preserved. This is in accordance with the teaching and philosophical principles of the Baduy tribe, namely "lojor does not cut off, hut does not connect".The preservation of the local wisdom of the Baduy Tribe is a sustainable effort that involves all elements of society. This tradition that has been passed down from generation to generation is not only a cultural heritage, but also a guide to life that is in harmony with nature and noble values. With various conservation efforts, it is hoped that the local wisdom of the Baduy Tribe can continue to be preserved and become an inspiration for the next generation.The application of local wisdom of the Baduy Tribe in maintaining the preservation of the Ciujung River is supported by customary values, traditions, dependence on rivers, and simple life. However, these conservation efforts are faced with various challenges, such as environmental changes, modernization flows, lack of government support, limited access, and different perceptions. Cooperation and synergy from various parties, including the government, academics, and non-governmental organizations, are needed to overcome this challenge and ensure the preservation of the Ciujung River and the local wisdom values of the Baduy Tribe. This research method uses a qualitative approach with a case study approach. Case studies use a variety of data sources to research, elaborate, and explain different aspects of an individual, group, program, organization, or event in a systematic manner. The conclusion is that the Baduy tribe does not exploit nature; They just use what is there and preserve. They believe that nature is an almighty trust that must be guarded and preserved.